Aminoacylation‐defective bi‐allelic mutations in human EPRS1 associated with psychomotor developmental delay, epilepsy, and deafness. Issue 3 (1st December 2022) - Jin, Danni; Wek, Sheree A.; Cordova, Ricardo A.; Wek, Ronald C.; Lacombe, Didier; Michaud, Vincent; Musier‐Forsyth, Karin
Abstract: Aminoacyl‐tRNA synthetases are enzymes that ensure accurate protein synthesis. Variants of the dual‐functional cytoplasmic human glutamyl‐prolyl‐tRNA synthetase, EPRS1, have been associated with leukodystrophy, diabetes and bone disease. Here, we report compound heterozygous variants in EPRS1 in a 4‐year‐old female patient presenting with psychomotor developmental delay, seizures and deafness. Functional studies of these two missense mutations support major defects in enzymatic function in vitro and contributed to confirmation of the diagnosis. Abstract : We report compound heterozygous variants in a bifunctional aminoacyl‐tRNA synthetase, EPRS1, in a 4‐year‐old female patient presenting with psychomotor developmental delay, seizures and deafness. Functional studies of these two missense mutations support major defects in enzymatic function in vitro and contributed to confirmation of the diagnosis.